Phenolic Contents and Antioxidant Activity of Helicteres Hirsuta Extracts - Hieu, Le T.; Thi, Tran T. V.; Son, Le Lam; Nhung, Nguyen Minh; Diep, Huynh Thi Ngoc; Mechler, Adam; Vo, Quan V. (Letters in Organic Chemistry, 2021)
Helicteres hirsuta, which belongs to the Malvaceae family, is used in traditional medicine to treat malaria, diabetes and cervical cancer. While these uses have not been validated in clinical studies thus far, extracts from H. hirsuta exhibit confirmed antioxidant and potential anti-cancer activity that warrant critical assessment. The aim of this study was to determine the antioxidant properties of different parts of the plant H. hirsuta. The antioxidant capacities of methanol extracts of different plant parts, and specific solvent fractions thereof were determined on the basis of 2,2-diphenyl−1−picrylhydrazyl (DPPH) radical scavenging and total antioxidant activity assays. The ethyl acetate fraction from the leaf material of H. hirsuta has the most potent antioxidant activity with the lowest half maximal inhibitory concentration (IC50) value of 9.50 μg/mL, that is 4 times lower than the IC50 of curcumin. The amounts of methyl gallate and rutin dominated the extracts at 8.62 ± 0.01 and 6.76 ± 0.02 mg/g, respectively, out of a total of 21.00 ± 0.01 mg/g active phenolic fraction. The amount of methyl gallate strongly correlated with total phenolic content and total antioxidant capacity, thus this compound may be useful as a marker of antioxidant activity in common medicinal plants
Keywords: HPLC